Seizures - Foyaca Sibat, Humberto (IntechOpen, 2018)
This book contains selected peer-reviewed articles that cover novel information on epileptic seizure and psychogenic non-epileptic seizures written by international researchers. In this book, we discuss self-reporting technologies for supporting epilepsy treatment. We also discuss about the diagnostic testing in epilepsy genetic clinical practice. Clinical aspects related to diagnosis in patients presenting psychogenic non-epileptic seizures vs. epileptic seizures and neurocysticercosis are discussed as well. We delivered novel aspects about the treatment for pseudoseizures. In another chapter, the authors estimated the prevalence of ischemic stroke in epileptic patients presenting subarachnoid neurocysticercosis and ischemic stroke frequency among HIV-positive patients, and finally other authors discuss autoimmune epilepsy, its new development, and its future directions. We are looking forward with confidence and pride to the remarkable role that this book will play for a new vision and mission.